The impact of decision aids in patients with colorectal cancer: a systematic review - Goldwag, Jenaya (BMJ Open, 2019)
OBJECTIVES: Our aim was to conduct a systematic review of the literature to determine the impact of patient decision aids (PDA) on patients facing treatment decisions for colorectal cancer. DESIGN: Systematic review. DATA SOURCES: Sources included Embase, Medline, Web of Science, CINAHL and the Cochrane Library from inception to June, 20, 2019. ELIGIBILITY CRITERIA: We included randomised controlled trials (RCTs), cohort studies, mixed methods and case series in which a PDA for colorectal cancer treatment was used. Qualitative studies were excluded from our review. DATA EXTRACTION AND SYNTHESIS: Following execution of the search strategy by a medical librarian, two blinded independent reviewers identified articles for inclusion. Two blinded reviewers were also responsible for data extraction, risk of bias and study quality assessments. Any conflict in article inclusion or extraction was resolved by discussion. RESULTS: Out of 3773 articles identified, three met our inclusion criteria: one RCT, one before-and-after study and one mixed-method study. In these studies, the use of a PDA for colorectal cancer treatment was associated with increased patient knowledge, satisfaction and preparation for making a decision. On quality assessment, two of three studies were judged to be of low quality. CONCLUSION: A paucity of evidence exists on the effect of PDA for colorectal cancer treatment with existing evidence being largely of low quality. Further investigation is required to determine the effect of decision aids for colorectal cancer treatment as well as reasons for the lack of PDA development and implementation in this area. PROSPERO REGISTRATION NUMBER: CRD42018095153.